1996
DOI: 10.1093/rheumatology/35.8.746
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Functional Disability in Early Rheumatoid Arthritis: A Cross-Sectional Study of 706 Patients in Four European Countries

Abstract: In this cross-sectional study of 706 European patients with rheumatoid arthritis (RA) of < or = 4 yr duration, we examined possible correlates of functional disability assessed by the Health Assessment Questionnaire. First, we examined a subsample of 237 Norwegian patients. The Ritchie index, sex, age, erythrocyte sedimentation rate (ESR) and disease duration correlated significantly with disability, whereas serum rheumatoid factor, hand X-ray changes and educational level did not. Subsequently, we cross-valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Several studies have found elevated levels of depression and anxiety in patients with RA in comparison with healthy controls [9][10][11]. A close association among pain, functional disability and psychological distress has been suggested by a number of authors [12,13]. Especially pain has been found to be closely associated with psychological distress and with depression in particular.…”
Section: Research Papermentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have found elevated levels of depression and anxiety in patients with RA in comparison with healthy controls [9][10][11]. A close association among pain, functional disability and psychological distress has been suggested by a number of authors [12,13]. Especially pain has been found to be closely associated with psychological distress and with depression in particular.…”
Section: Research Papermentioning
confidence: 96%
“…The pain subscale contains eight items referring to the experience of pain. Each item can be answered either yes or no, with a theoretical range of [8][9][10][11][12][13][14][15][16]. The sum of all answers creates the total score [41].…”
Section: Painmentioning
confidence: 99%
“…ESR is less likely to be abnormal than any of the other 6 Core Data Set measures for RA, including joint counts, questionnaire scores, and global measures, as noted in several recent poster presentations at the ACR and EULAR annual meetings. We recently recognized data from 4 additional sites from the early 1990s from the EURIDISS (European Research on Incapacitating Diseases and Social Support) study 8 , in which the mean ESR was < 30 mm/h in RA patients from Oslo (Norway), Nancy (France), Groningen (The Netherlands), and Belfast (Northern Ireland), now bringing to 7 the total number of locales with similar findings (Table 1).…”
Section: Dr Pincus Et Al Replymentioning
confidence: 71%
“…A report in 1994, indicated a normal ESR was found in about 40% of patients [28]. A 1996 report indicated mean ESR levels of 30 or less (normal for females who are 70% of RA patients) in 4 European settings in Norway, the Netherlands, Northern Ireland, and France [29]. A 2007 report indicated that ESR and CRP were normal in about 40% of patients from the USA and Finland (Table 2) [30].…”
Section: ) Some Limitations Of Laboratory Tests In Ramentioning
confidence: 99%